Maxillofacial Trauma in Children - Mukherjee, Chitrita Gupta (Jaypee Brothers Medical Publishers, 2012)
Pediatric trauma involving the bones of the face is associated with severe injury and disability. Although much is known about the epidemiology of facial fractures in adults, little is known about injury patterns and outcomes in children. The most common facial fractures were mandible, nasal and maxillary/zygoma. The most common mechanisms of injury are motor vehicle collisions, violence and falls. These fracture patterns and mechanisms of injury varies with age. Cranial and central facial injuries are more common among toddlers and infants, and mandible injuries are more common among adolescents. Although bony craniofacial trauma is relatively uncommon among the pediatric population, it remains a substantial source of mortality, morbidity and hospital admissions. Continued efforts toward injury prevention are warranted. An overview of various types of fractures and their management modalities is discussed, with case reports. How to cite this article: Mukherjee CG, Mukherjee U. Maxillofacial Trauma in Children. Int J Clin Pediatr Dent 2012;5(3):231-236.